A hybridization-triggered DNAzyme cascade assay for enzyme-free amplified fluorescence detection of nucleic acids. Issue 1 (14th November 2018) - Wang, Huizhen; He, Dinggeng; Wu, Ri; Cheng, Hong; Ma, Wenjie; Huang, Jin; Bu, Hongchang; He, Xiaoxiao; Wang, Kemin
Abstract : An enzyme-free and ultrasensitive fluorescence assay for the detection of nucleic acids was successfully established by a hybridization-triggered DNAzyme cascade (HTDC). Abstract : An enzyme-free and ultrasensitive fluorescence assay for the detection of nucleic acids was successfully established by a hybridization-triggered DNAzyme cascade (HTDC). This simple and cost-effective sensor has good sensitivity, selectivity and the capability for detection of target DNA from complex fluids.